(untitled) (Eurasian Medical Research Periodical, 2022)
Our tests were performed on 104 COVID-19 patients between the ages of 2 and 75. The diagnosis of COVID-19 has been confirmed based on clinical, epidemiological and laboratory findings. The patients studied were mainly those who had the disease in May-June 2021, and their age was as follows: 1 person 1 year, 2 people 3 years, 1 person 6 years old, 1 person 11 years old, 1 person 17 years old, 1 person 19 years old, 1 person 22 years old, 9 people 24 years old, 19 people 30-34 years old, 6 people 39 years old, 6 people 40-44 years old, 3 people 45-49 years old, 8 people 50-55 years old, 11 people 55- 59 years old, 10 people 60-64 years old, 16 people 65-69 years old, 11 people over 70 years old. On the skin and mucous membranes of the observed patients, roseola and vascular spots were noted in 42%, urtica - in 8%, petechiae - in 9%, papules - in 10%, bulla - in 12%, erosion - in 10%, skin ulcers - in 9%.